Developing a systems engineering concept for digitalizing higher education institutions - Teslia, Iurii; Yehorchenkova, Nataliia; Khlevna, Iulia; Kataieva, Yevheniia; Latysheva, Tatiana; Yehorchenkov, Oleksii; Khlevnyi, Andrii; Veretelnyk, Vitaliy (Eastern-European Journal of Enterprise Technologies, 2020)
The systems engineering concept of digitalization of higher education institutions (HEI) was proposed. The concept integrates the systemic, process-based, and project-based approach to displaying the objects and processes of the HEI activity in a unified digital space. This will make it possible to use it for automated solutions of functional problems in the educational, scientific, economic, and management processes of the HEI. Within the framework of the concept, the approaches to implementation were proposed: processes of the HEI digital transformation; functions and structures of the HEI digitalization project management; tools of a digital university. The concept is based on a unified digital space, which includes: digital and functional environment, tools for its formation, tools for using the digital environment. It was shown that the success of the transformation of the HEI into a digital university directly depends on the effectiveness of the organization of processes of digitalization project management. And this requires the use of the problem-oriented methodology of project management; the creation of a special division of the HEI digitalization; the development of the structure and technology of filling and using the digital space of an institution of higher education. The result of the application of the HEI digitalization concept is the creation of the specified methodology for project management, which is focused on the digital transformation of an institution of higher education. New organizational principles of digitalization of higher education institutions were proposed, based on the project-oriented organizational structure – a digital transformation office. The structure and the functions of such an office were determined. The processes of higher education institutions from the positions of readiness for the implementation of the systems engineering concept of digitalization were explored. Examples of the HEI digitalization using the proposed concept were given